Pembelajaran HOTS dalam Perspektif Pendidikan Islam - Amini Amini; Annisa Nurjannah (Journal on Education, 2023)
Basically the HOTS assessment must begin with HOTS learning as well. The results obtained based on the basic observations still found that (1) some teachers still need updating about knowledge, especially the 2013 curriculum, (2) approximately 45% of students are still passive when taught and class activity is often dominated by smart children, (3 ) in the learning process the questions made by the teacher were mostly still at the C1-C3 level, and (4) the students' ability to think critically and analytically was very lacking. Based on the analysis of these problems, the purpose of this study was to analyze HOTS learning and assessment in the perspective of Islamic education